(untitled) (Journal of Foreign Language Studies, 2022)
This article presents the experience of a team in their implementation of a ministerial research project to develop a mobile application for English language learning for Vietnamese teenagers. This study utilizes Berge’s (1997) model of online facilitator roles, and Stark and Luttuca’s (1997) framework on academic plans to analyze secondary materials such as meeting minutes, Zalo messages, and personal experiences of the team members in developing a mobile application for English language learning at A2 and B1 levels (equivalent to levels 2 and 3 of Vietnam’s language proficiency framework). The study results reveal the significance of three factors: team collaboration, coordinator’s role, and initiatives in developing a mobile application for English language learning. This study offers some practical implications for teambased collaboration between the subject matter experts and technical specialists in an interdisciplinary research project.